Development stressors are stronger than protected area management: A case of the Pantanos de Centla Biosphere Reserve, Mexico. (September 2017) - Rosa-Velázquez, Mayra Isabel De la; Espinoza-Tenorio, Alejandro; Díaz-Perera, Miguel Ángel; Ortega-Argueta, Alejandro; Ramos-Reyes, Rodimiro; Espejel, Ileana
Highlights: Coastal reserves are threatened by multi-cause and –scale drivers of land-use change. The conservation of flooded forests is the main challenge to the Centla Reserve. In Centla Reserve, combatting core causes of habitat destruction is self-defeating. Reserves should be integrated into broader landscape coastal management strategies. Land-use change evaluation in reserves is urgently needed to collect lessons-learned. Abstract: Evaluation of the management effectiveness of protected areas has become a global priority, especially in coastal zones, where essential services are threatened by land use pressures. To assess the effectiveness of a coastal protected area, we estimated the land-use change (LUC) within and outside of the Pantanos de Centla Biosphere Reserve (PCBR) and interviewed key stakeholders to identify the main stressors causing LUC. The native vegetation cover under the PCBR protection decreased by 65% over 24 years; whereas agriculture and livestock lands doubled, even within the core conservation areas of the PCBR. The greatest loss was in the flooded forest (48%), where the reduction was similar in and around the reserve. The effectiveness of reserve management was affected by drivers of land use change, which include agricultural and livestock enterprises that are run by government programs. Effective management of the PCBR has been undermined by poor management practices, limited capacity and resources, and inadequate zoning design. Protected areas and its surrounding landscapes could be considered to be natural experiments for future research, where high value land uses and conservation objectives coincide within coastal areas that will face a predicted sea level rise, more intense floods and higher temperatures.